Frequency Level and Problems encountered by the IBED Faculty in Utilizing the Google Workspace for Education - Lanzon, Roxanne Cel (JPAIR Institutional Research, 2022)
The majority of global sectors were affected by the pandemic caused by a Coronavirus outbreak. This includes the academic world, which consists of millions of enrolled students and active teachers who previously had regular classes in their institutions but were forced to stay home due to the pandemic. To continue the educational process, most countries implemented online classes. Both teaching and learning take place in this mode using electronic devices and different online platforms relatively new to the teaching-learning community. The study used a quantitative method where the researcher surveyed the IBEd Faculty at St. Mary’s College of Baliuag to determine the frequency of educational technology tools such as Google Workspace for Education. A survey was conducted to evaluate the frequency of utilization and problems encountered by the Faculty in utilizing the Google Workspace Educational Tools. Results showed that the faculty were unfamiliar with some of the tools in Google Workspace and rarely used them in their classroom discussion. Teachers' responses revealed that they still need time to explore more of the different tools in Google Workspace and attend different pieces of training that will teach them how to use the tools. The results of the survey will provide valuable information in the design of professional training programs.
Keywords: Education; Educational Technology; Google Workspace for Education; Google Workspace Education Tools; Philippines